ANALISIS HUBUNGAN PENGETAHUAN DAN SIKAP TENAGA KESEHATAN DENGAN PENERAPAN SISTEM MANAJEMEN KESEHATAN DAN KESELAMATAN KERJA RUMAH SAKIT (SMK3RS) DI RSU SEMBIRING DELI TUA KAB.DELI SERDANG - Ripai si regar (Jurnal Penelitian Kesmasy, 2020)
Hospital staff have a greater risk of accidents and occupational diseases than other industrieal. The research problem is to analyze the up optimal the implementation of the Hospital Occupational Safety and Health Management System (HOSHMS). The research objective was to analyze the relationship of psychological behavior (knowledge and attitudes), as well as those related to the application of implementation of the Hospital Occupational Safety and Health Management System. This type of research is an explanatory research approach. Population is all health workers as many as 399 people and up to 80 people in hospital Sembiring Deli tua.The Data were collection through questionnaires and action observations. Univariate and bivariate data were analyzed by using chi-square , while multivariate data used multiple linear regression tests at significance level of 95%. The results of the study showed that the implementation of implementation of the Hospital Occupational Safety and Health Management System (HOSHMS),was ineffective (52.2%) and effective (47, 5%). The results of the test show all of the above independent variables related to the application of implementation of the Hospital Occupational Safety and Health Management System (HOSHMS). The knowledge is the most dominant variable with a coefficient of 0.013 with Exp (B) 4,051 95% CI (1,348-12,175). To optimize the application of implementation of the Hospital Occupational Safety and Health Management System (HOSHMS), it is recommended that management continue to be continuously committed in providing resources; implementing a bottom-up system in planning and implementation; improve all forms of communication .